Electromagnetic Waves - Inan, Umran S.; Inan, Aziz. (Upper Saddle River Prentice Hall, 2000)
Demonstrates how electromagnetic concepts are important to modern electrical engineering applications. Detailed examples, selected application examples, abundant illustrations, and numerous end-of-chapter problems emphasizing practical applications. For electrical engineers interested in electromagnetics.